Microbial community changes in TNT spiked soil bioremediation trial using biostimulation, phytoremediation and bioaugmentation - Nõlvak, Hiie; Truu, Jaak; Limane, Baiba; Truu, Marika; Cepurnieks, Guntis; Bartkevičs, Vadims; Juhanson, Jaanis; Muter, Olga (Journal of Environmental Engineering and Landscape Management, 2013)
Trinitrotoluene (TNT), a commonly used explosive for military and industrial applications, can cause serious environmental pollution. 28-day laboratory pot experiment was carried out applying bioaugmentation using laboratory selected bacterial strains as inoculum, biostimulation with molasses and cabbage leaf extract, and phytoremediation using rye and blue fenugreek to study the effect of these treatments on TNT removal and changes in soil microbial community responsible for contaminant degradation. Chemical analyses revealed significant decreases in TNT concentrations, including reduction of some of the TNT to its amino derivates during the 28-day tests. The combination of bioaugmentation-biostimulation approach coupled with rye cultivation had the most profound effect on TNT degradation. Although plants enhanced the total microbial community abundance, blue fenugreek cultivation did not significantly affect the TNT degradation rate. The results from molecular analyses suggested the survival and elevation of the introduced bacterial strains throughout the experiment.First published online: 15 Feb 2013